Synthesis and characterization of graphene oxide-based nanomaterials using oil palm leaves and tea leaves wastes - Mohd Shaifuddin, Muhammad Amir Faiz (2022)
Graphene, which is considered as a unique material due to having an excellent electron conductivity and having the potential as coupling agent with photocatalyst. Despite of that, the challenges came in when consider the cost to mass produce as it will be expensive. Besides, there is a rising concern for the environment when it comes to converting GO to RGO as a cheap alternative to pristine graphene. This is because of the harmful chemicals is conventionally used to reduced GO into RGO. Hence, the objective of the first part of this research was to synthesized graphene oxide (GO) from tea waste as a replacement for commercially available graphite. Then, RGO/TiO2 was synthesized and the rate of degradation for methyl orange (MO) was observed as the ratio between GO and TiO2 change. The conversion of tea waste biomass was carried via carbonization at high temperature and further used as starting material to produce graphene oxide (GO). The oxidation and exfoliation of graphitized carbon was successfully achieved using modified Hummer’s method. The as synthesized GO was loaded with titanium dioxide nanoparticles (TiO2) using hydrothermal method to produce RGO/TiO2. The prepared nanocomposites were characterized by means of XRD, FTIR, Raman and FESEM analysis. The evaluation for RGO/TIO2 nanocomposite photocatalytic activity was carried out based on degradation of methyl orange (MO) under the ultraviolet (UV) light irradiation. Results obtained using FTIR results revealed the successful oxidation of graphitized carbon with the presence of carboxyl and hydroxyl group. FESEM images suggested the changes of surface morphology from graphite flakes structure into few layers of graphene sheets. Therefore, it can be indicated that graphitized tea waste has the potential to be an alternative replacement for commercial graphite as a precursor to synthesis the GO. Moreover, GO obtained has immense potential for degradation of various water pollutants when combined with TiO2. Photocatalytic activity experiment inferred that the importance of optimum ratio between GO to TiO2 which can resulted in difference in the degradation efficiency; RGO/TiO2 1:8 > RGO/TiO2 1:4 > TiO2 > RGO/TiO2 1:6 > RGO/TiO2 1:10. In the second part of the project, graphite was used as starting material and was oxidized using modified Hummer’s method. The oil palm leaves extract was utilized as an alternative reducing agent to produce reduced graphene oxide. This is due to a rising concern on the usage of conventional reducing agent which is harmful towards the environment. The oil palm leaves extract with the mixture of graphene oxide (GO) solution was refluxed to produce reduced graphene oxide (RGO). The as-synthesized green approach RGO material were then characterized using X-ray diffraction (XRD), UV visible spectroscopy (UV-Vis), energy dispersive X-ray (EDX), transmission electron microscopy (TEM), and Raman spectroscopy. The results revealed that the interspace distance between plane increased proportionally as graphite was oxidized, increasing from 0.33 nm to 0.84 nm. The reduction process of GO using oil palm leave extract showed the success in removing the hydroxyl group and amorphization of sp2 carbon structures. The reduction process resulted in increase of C/O ratios from 1:1 to 3:1. Raman spectroscopy revealed that the G band position was restored comparable to graphite as the reduction process successful achieved. TEM images and selected area electron diffraction (SAED) patterns illustrated the confirmation of the successfully synthesized of the monolayer of graphene sheet. Electrochemical studies carried out for both GO and RGO have positively differentiated and concluded a better voltage-current response of RGO in comparison to GO. The as synthesized RGO in the current project holds various potential for further investigation and industrial applications not limited to just supercapacitor and photocatalyst.